PEMANFAATAN JAMUR PELARUT FOSFAT DAN MIKORIZA UNTUK MENINGKATKAN KETERSEDIAAN DAN SERAPAN P TANAMAN JAGUNG PADA TANAH ALKALIN - Rizky Mardiana Nasution; T. Sabrina; Fauzi Fauzi (Jurnal Agroekoteknologi, 2014)
P availability in soil is often be the limiting factor on plant growth and production. Phosphatesolubilizing organism is one of alternative to solve this problem. The aim of this study was todetermine the effect of phosphate solubilizing fungi and mycorrhizae and their interaction toincrease P availability and P absorption by Maize on Alkaline Soil . This research was conducted inthe green house, Soil Biology laboratory and Chemical and Soil Fertility Laboratory of FakultasPertanian USU in March-August 2013, used Randomized Block Design (RBD) factorial consistingof 2 factors and 4 replications. The first factor was phosphate solubilizing fungi inoculationconsisting of 2 treatments (with and without inoculation) and the second factor was mycorrhizaeapplication consisting of 3 treatments (0, 10, 20 g/polybag). Parameters observed were soil pH,P-availability, C-organic, plant height, stem diameter, shoot dry weight, root weight, P-absorption,100 seeds dry weight, mycorrhizae infection and phosphate solubilizing fungi population. Theresult showed that phosphate solubilizing fungi inoculation significantly affected phosphatesolubilizing fungi population and not affected others parameters, however it increased plant growthand production. Mycorrhizae application decreased soil pH, stem diameter, and increasedmycorrhizae infection significantly. Mycorrhizae application dose of 10 g mycorrhizae resulted thehighest plant height, shoot dry weight, highest P-absorbtion, 100 seeds dry weight but decreasedC-organic and P availability.Keywords: phosphate solubilizing fungi, mycorrhizae, alkaline soil, maize